2019
DOI: 10.1080/13696998.2019.1651122
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of denosumab for the prevention of skeletal-related events in patients with solid tumors and bone metastases in the United States

Abstract: Aims: Bone complications (also known as skeletal-related events [SREs]) pose significant health and financial burdens on patients with bone metastases. Denosumab demonstrated superiority over zoledronic acid in delaying the time to first SRE. This study examined the lifetime cost-effectiveness of denosumab vs zoledronic acid from both US payer and societal perspectives. Methods: This analysis used a lifetime Markov model and included patients with breast cancer, prostate cancer, and other solid tumors and bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 61 publications
3
15
0
7
Order By: Relevance
“…48 These findings may have been caused by the following: (1) ZA has been applied in clinical practice for many years, and it can be difficult to change prescribing practices; and (2) the cost of denosumab treatment is relatively higher, although pharmacoeconomic research has indicated that denosumab is a cost-effective BTA. 49 From a societal perspective, compared with ZA, denosumab treatment is a cost-effective option, with an incremental cost of 9043 USD, an incremental benefit of 0.128 quality-adjusted life-years, and a net monetary benefit of 10,135 USD. 49 Furthermore, a study in clinical practice carried out in Germany concluded that denosumab was associated with greater medication persistence and better compliance compared with a bisphosphonate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 These findings may have been caused by the following: (1) ZA has been applied in clinical practice for many years, and it can be difficult to change prescribing practices; and (2) the cost of denosumab treatment is relatively higher, although pharmacoeconomic research has indicated that denosumab is a cost-effective BTA. 49 From a societal perspective, compared with ZA, denosumab treatment is a cost-effective option, with an incremental cost of 9043 USD, an incremental benefit of 0.128 quality-adjusted life-years, and a net monetary benefit of 10,135 USD. 49 Furthermore, a study in clinical practice carried out in Germany concluded that denosumab was associated with greater medication persistence and better compliance compared with a bisphosphonate.…”
Section: Discussionmentioning
confidence: 99%
“…49 From a societal perspective, compared with ZA, denosumab treatment is a cost-effective option, with an incremental cost of 9043 USD, an incremental benefit of 0.128 quality-adjusted life-years, and a net monetary benefit of 10,135 USD. 49 Furthermore, a study in clinical practice carried out in Germany concluded that denosumab was associated with greater medication persistence and better compliance compared with a bisphosphonate. 50 The convenience of a subcutaneous route of administration and a more favorable tolerability profile could be the reasons for those findings.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal-related events result in the use of significant healthcare resources, 37 and the prevention of skeletal-related events has been shown to reduce healthcare costs. 38 Our centre is carrying out a randomised study comparing standard of care versus palliative radiotherapy for asymptomatic but high-risk skeletal metastases, with a primary endpoint of reducing the rate of skeletal-related events (NCT03523351). Although most of this review focusses on the roles of MDT in prolonging OS or PFS, quality of life and healthcare-costrelated endpoints are important parameters to consider as trials intended to prevent adverse events from metastases are developed.…”
Section: Sabr and Immunotherapymentioning
confidence: 99%
“…For example, another study, which was based on SRE reductions reported from the pivotal phase 3 denosumab trials, summarized that, while the direct costs of using denosumab are much higher than for zoledronic acid, the reduced costs associated with bone complications actually favored denosumab. (59) Results from these studies also appear to be at the risk of being biased dependent on their financial sponsor (summarized in Shapiro and colleagues (58) and Koo and colleagues (60) ).…”
Section: Socioeconomic Considerationsmentioning
confidence: 99%